Blunt and Penetrating Injury to the Bowel: A Review - Skelhorne-Gross, Graham; Kenny, James (Clinics in Colon and Rectal Surgery, 2023)
Traumatic injuries to the small and large bowel are common and can be highly morbid. Identifying these injuries, especially in stable patients who suffer blunt trauma, can be challenging. It is critical that traumatic bowel injuries are diagnosed in a timely fashion as delays in diagnosis and treatment are associated with worse outcomes. The literature outlining the management of traumatic bowel injuries is mostly comprised of retrospective data and case reports/series. We have compiled the existing literature and relevant guidelines into a single resource for providers who care for traumatically injured patients.
Keywords: gastrointestinal fluid; abdominal trauma; bowel injury